Citizens imprisoned : Japanese internment camps - Loh-Hagan, Virginia (Loh-Hagan, Virginia. Behind the curtain., 2020)
Presents an illustrated two-act play for students to perform that retells key facts about the Japanese internment camps during World War II. Includes historical background, fact boxes, a timeline of events, vocabulary words, and critical thinking questions.